Wartość godziwa - wybrane problemy - Mazur, Alicja (Some aspects of fair value, 2008)
It is controversial to think about fair value as this is the category of measurement which ensures the achievement of the financial statement’s object which is decision usefulness. Questionable is the reliability of the fair values assigned on the basis of imperfect markets or on the basis of model assumption in case of lack of such markets. The fair value will also not reflect in the financial statements the synergy effects resulting from combined usage of assets. And this information might be especially needed by investors for decision making. Another doubt arises in connection with the reflecting of fair value’s changes in financial statements. Inconsistency of regulations in this matter might mislead the recipients of financial statements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 65-73